Peningkatan Minat Bercocok Tanam Peserta Didik TK Metta Maitreya Pekanbaru Menggunakan Teknologi Hidroponik - Rida Jelita; Hosan Hosan; Irawati Irawati (Jurnal Maitreyawira, 2021)
The research was motivated by the low level of interest of students in farming activities because the students' perceptions of farming were identical to land, dirty, requiring a lot of energy, heating under the hot sun and other things that made students reluctant to participate in farming activities. planting. The aim of the study was to determine the increase in interest in planting the participants in the Kindergarten Metta Maitreya using hydroponic technology. The research method used is qualitative and using descriptive analysis. The focus of this research is on the interest in cultivating students through hydroponic farming. The data were collected by several methods, including: observation, interviews, questionnaires and documentation. The results of the study obtained data that the participants' interest in farming at Metta Maitreya Kindergarten increased after the treatment, seen from the questionnaire value which increased by 6.03% from 79.17 to 85.2 in the very good category. The increasing interest in cultivating students was also supported by the results of observational research of 12.4 with good categories, interviews and documentation which obtained the same results. KATA KUNCI : Minat Bercocok Tanam, Teknologi Hidroponik, TK Metta Maitreya